Efektifitas Pemberian Telur Terhadap Peningkatan Kadar Hemoglobin Ibu hamil di Puskesmas Paccellekang Gowa - Palulungan, Ratni; Masni, Masni; Wilma, Wilma; Basir, Muhammad; Baso, Bahtiar; Darsim Gaffar, Herry (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The iron content in eggs can help increase hemoglobin levels. The purpose of this study was to determine the effectiveness of giving eggs to the increase in hemoglobin levels of pregnant women at Pacellekang Gowa Public Health Center. The research method used was experimental quasy with one-group pretest-posttest design. The population in this study were pregnant women in the health center area. The sample consisted of 16 mild anemia pregnant women using purposive sampling technique. The research data was taken using the observation sheet and the test used in this study was the Paired sample T-test. The results of the statistical test of hemoglobin levels before and after being given boiled eggs with an average before was 10,163 and after giving eggs an increase in Hb levels to 11,206. From the results of the Paired Sample T-Test, the value of ρ = 0.000 was obtained. The value of ρ is smaller than the value of α = 0.05 (ρ = 0.000 <α = 0.05). Based on the value of ρ value, it can be concluded that there is an effect of consumption of boiled eggs on the increase in Hb levels in pregnant women at Pacellekang Gowa Health Center in 2019, thus Ho is rejected and Ha is accepted.